Interaction of the Arabidopsis GTPase RabA4c with Its Effector PMR4 Results in Complete Penetration Resistance to Powdery Mildew - Ellinger, Dorothea (American Society of Plant Biologists, 2014)
The (1,3)-β-glucan callose is a major component of cell wall thickenings in response to pathogen attack in plants. GTPases have been suggested to regulate pathogen-induced callose biosynthesis. To elucidate the regulation of callose biosynthesis in Arabidopsis thaliana, we screened microarray data and identified transcriptional upregulation of the GTPase RabA4c after biotic stress. We studied the function of RabA4c in its native and dominant negative (dn) isoform in RabA4c overexpression lines. RabA4c overexpression caused complete penetration resistance to the virulent powdery mildew Golovinomyces cichoracearum due to enhanced callose deposition at early time points of infection, which prevented fungal ingress into epidermal cells. By contrast, RabA4c(dn) overexpression did not increase callose deposition or penetration resistance. A cross of the resistant line with the pmr4 disruption mutant lacking the stress-induced callose synthase PMR4 revealed that enhanced callose deposition and penetration resistance were PMR4-dependent. In live-cell imaging, tagged RabA4c was shown to localize at the plasma membrane prior to infection, which was broken in the pmr4 disruption mutant background, with callose deposits at the site of attempted fungal penetration. Together with our interactions studies including yeast two-hybrid, pull-down, and in planta fluorescence resonance energy transfer assays, we concluded that RabA4c directly interacts with PMR4, which can be seen as an effector of this GTPase.